Application of Integrated Kano’s Method and Quality Deployment Function in New Product Development Process - Arshad, Nurul Hidayah; Arep @ Ariff, Hambali; Samsudin, Abdul Rahim; Minhat, Mohamad (2011)
Staying competitive in the fast growing is becoming more challenging. Every new product development is fundamental for any company but the quick launching time and meeting customers expectation is essentials. To stay competitive, one has to have a systematic way of new product development and have an effective approach to understand customer requirements better translate into new and improved product. Quality Function Deployment (QFD)method can be help to gather customer demands and link to the product design in a systematic way. Integrating Kano's Model result from the questionnaires into QFD framework, provide a deeper perspective of "hidden" customer needs that leads to a better product design. The objective of this study is to implement the integrated method Kano's Model and QFD on a new vegetable cutting machine blade cleaner development.